Molecular docking study of some active principles from Silybum marianum, Chelidonium majus, ginkgo biloba, gelsemium sempervirens, Artemisia annua, and taraxacum officinale - Daniel Cord; Mirela Claudia Rimbu; Cristiana Tanase; Cristina Tablet; Gheorghe Duca (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry)

(untitled)
In this study, it was investigated by molecular docking, the interaction of fourteen natural compounds (artemisinin, bilobalide, bilobetin, chelerythrine, chelidonin, epicatechin, gelsemic acid, ginkgolide A, isosilybin, silicristin, silybin, taraxacin, taraxacoside, and taraxinic acid) from Silbum marianum, Chelidonium majus, Ginkgo biloba, Gelsemium sempervirens, Artemisia annua, and Taraxacum officinale with three cancer-related GPCRs: the apelin receptor, the β2-adrenoceptor, and the A2B adenosine receptor. QuickVina2 was used to determine the binding affinities and identify the nature of the strongest interactions. Several compounds (bilobetin, isosilybin, chelidonin, silicristin, and artemisinin) showed high binding affinities and interactions with key residues responsible for the receptor activity. These results highlight the potential of phytochemicals in modulating the activity of GPCRs and may form the basis for further experimental validation.